2011
DOI: 10.1111/j.1600-0536.2011.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal sensitivity in patients with orthopaedic implants: a prospective study

Abstract: Given the discrepancies between the information obtained while taking patient histories and test results, preoperative history-taking alone appears to be insufficient for identifying patients with metal sensitivity. Moreover, the increase in the percentage of patients who tested positive for metal sensitivity 1 year post-implantation suggests the possibility of prosthesis-induced sensitization. Therefore, objective determination of metal sensitivity at preoperative assessment should be considered in planning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 27 publications
4
104
1
3
Order By: Relevance
“…One study used LTT [47], one study used a combination of patch test and LTT [22], two studies used neither of these tests [8,10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study used LTT [47], one study used a combination of patch test and LTT [22], two studies used neither of these tests [8,10].…”
Section: Resultsmentioning
confidence: 99%
“…Seventy articles were excluded after reviewing the title and abstract (some exclusion criteria: other joints than knee, allergic reaction to medication during surgery, infection, antibiotics, metallosis, and allergic reaction to suture material after surgery). Forty-six articles were included in the review: 17 case reports (Table 1), 4 reviews [5,15,42,43], 16 retrospective articles [11,17,19,26,32,33,35,41,45,46,48,51,52,54,61,63], 8 prospective articles [2,8,10,22,25,40,47,69], and one "expert opinion" [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…implant one year post-implantation [17]. Furthermore, Waterman et al [18] noted positive tests results in 8 out of 85 (9.4%) patients undergoing hip replacement.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the probability of developing a metal allergy was higher after surgery (OR, 1.52; 95%CI, 1.06-2.31) and that the risk was even higher when failed implants were compared with stable total joint replacements (OR, 2.76; 95%CI, 1.14-6.70) [25]. A few recent prospective studies have also suggested an increase in cases of metal allergy following THA, even in patients with well-functioning prostheses [26][27][28].…”
Section: The Rising Potential Impact Of Metal Hypersensitivitymentioning
confidence: 99%